Hierarchical Facility Location Model for allocating cancer treatment units in interior of Rio de Janeiro - Isabella Fischer Guindani Vieira; Matheus Ferreira de Barros; Allan Cormack (Production)
Abstract Paper aims This work aims at proposing a mathematical model for allocation of oncological treatment units of SUS. Originality A model of the same architecture was not found in the literature for the delimited problem. Research method The mathematical models of location in the literature were reviewed and based the choice by the two-level hierarchical pq-median model with additional constraints of maximum distance and vertices eligibility, which was implemented in the CPLEX optimization software. Main findings Satisfactory results with homogeneous networks, centralized facilities in their service area and shorter distance traveled by users indicate the efficiency of the model in determining the optimum location given the number of facilities to be allocated. Implications for theory and practice The model proved to be an efficient tool to assist health managers in their decision-making about the network of facilities, not just oncological, but of any nature and many others public sectors.